Petrogenesis of late Cretaceous granitoids in Gemici (Elazig-Türkiye): evidence from whole-rock geochemistry, Sr-Nd isotopes, zircon U-Pb dating, and trace elements - Sar, Abdullah (Pergamon-Elsevier Science Ltd, 2025)
The late Cretaceous granites and granodiorites are exposed in the Gemici area of Elazig Province (eastern T & uuml;rkiye). Here, we present recent whole-rock major oxide, trace element and Sr-Nd isotopic analyses, as well as zircon U-Pb data and trace element data of granitoids from the Southeastern Anatolian Orogenic Belt (SAOB) in eastern T & uuml;rkiye. This paper aims to investigate the petrogenesis of the late Cretaceous granite and granodiorites (Gemici/Elazig) using new and previously existing geochemical and geochronological data. Geochemical data indicate that the studied granites and granodiorites vary in composition from metaluminous to peraluminous, exhibit tholeiitic-calc-alkaline characteristics, and belong to the I-type granite. m. The Th/U ratios of zircon grains suggest a magmatic origin. Negative Eu and positive Ce values in zircon grains are indicative of unaltered magmatic zircons. The studied rocks exhibit a narrow range of 87Sr/86Sr(i) ratios (0.704369-0.706019), and epsilon Nd(t) values vary from 2.9 to 6.2, yielding model ages (TDM) ranging from 841 to 1421 Ma. The energyconstrained assimilation-fractional crystallization (EC-AFC) modelling shows that the studied granite and granodiorites contain 1 %-5 % crustal melt contributions. Geochemical data indicate that subduction zone magmatism plays an active role in the petrogenesis of the studied rocks.
Keywords: Zircon U-Pb data; Zircon trace elements; Sr-Nd isotopes; Petrogenesis; Gemici; Elazig